The “Pfizer Boob Job”: A Case of Unexplained Gigantomastia - Oluwatoba T. Balogun, BMSc; Beverley Osei, BHSc; Kathleen A. Armstrong, MSc, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. True parenchymal breast changes following COVID-19 vaccination are exceedingly rare. Equally rare are incidences of pseudoangiomatous stromal hyperplasia (PASH)–associated gigantomastia. The patient in this case report presented with both occurrences and experienced massive breast enlargement 1 week postadministration of the Pfizer/BioNTech COVID-19 vaccine, which worsened after her second dose. Definitive treatment was achieved through reduction mammoplasty, with the final pathology report confirming uniformly dense terminal duct lobular units with interspersed PASH units. The association between the COVID-19 vaccine, PASH, and breast hypertrophy warrants further investigation to comprehend the spectrum of reactions to the vaccine.